KEPUTUSAN MAHASISWA DALAM MELAKUKAN PEMBELIAN MELALUI APLIKASI SHOPEE - Wandita, Fransiska Helen; Wardianto, K Bagus; Nugeraha, Prasetya (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
Digitalization in business creates a new paradigm in the buying decision process. Consumer decisions are no longer limited to product quality and price as described by Tjiptono (2008). The online consumer purchasing decision model for students in this study is strongly influenced by sales promotion, online customer reviews, and customer trust where when this variable forms the level of determination it reaches 68. This study was conducted on 100 student respondents using the Shopee application which was taken using the purposive sampling method. based on the number of purchases in a month and has an income of less than 2 million rupiah. The results of this study explain that the online purchase stage is carried out when the respondent has reviewed and compared the promotions available in the marketplace. Then the final stage is to rank the available product options based on the highest level of confidence.